Usability and validity of a child development inventory in Filipino for early identification of children with disabilities - Ng, Rodolfo C. (Animo Repository, 2005)
A descriptive-evaluative method of research was conducted which aimed at investigating the usability and validity of translated Filipino Child Development Inventory for early identification of children with disabilities. The study involved 30 respondents who were parents or caregivers and their children with developmental problems or concerns and was conducted at the High Risk Clinic of Bulacan Provincial Hospital in Malolos, Bulacan. The study revealed that the majority of the respondents are college graduates yet unemployed, Tagalog speaking mothers whose ages range between 21-30 years old. Young children who were in their first three years of life of both sexes comprise the majority with developmental problems or concerns. Their common problems or concerns in the order of frequency are: (1) does not talk well for age, (2) cannot sit still maybe hyperactive and (3) does not pay attention poor listener and disorganized messy, careless, irresponsible. The study also identified three developmental items in the original Child Development Inventory that need to be modified because of cultural and language differences. These are (1) item #60, washes self in bathtub, (2) item # 62, uses table knife for spreading, and (3) item #154, uses irregular plurals correctly. In terms of validity, the study proved to demonstrate that the translated Filipino Child Development Inventory is valid with sensitivity of 95% and specificity of 75%. Furthermore, the translated Filipino Child Development Inventory also showed that it is usable to the end users as a developmental assessment tool among non-English speaking respondents. Based on the above findings and conclusions, it is recommended that the parent-completed instrument, the translated Filipino Child Development inventory is valid and useful both as a screening and as an assessment tool for early identification of children at risk or with known risk for disabilities. It is also recommended that the same instrument can also be used as surveillance tool for monitoring the progress of the intervention.